The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/adem.201700547
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Spheres Incorporated Aluminum/Poly (Vinylidene Fluoride) for Enhanced Burning Propellants

Abstract: In this paper, we demonstrate that preparation by electrospray deposition of mesoporous SiO 2 particles can be employed as additives to Aluminum/Poly (Vinylidene Fluoride) (Al/PVDF) to enhance reaction velocity. We find that the reaction velocity of Al/PVDF with 5 wt% SiO 2 is 3Â higher. The presence of meso-SiO 2 appears to accelerate the decomposition of PVDF, with a significant increase in HF release, resulting in higher heat release. We believe that hot-spots around meso-SiO 2 may serve as multiple ignitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…A contrasting phenomenon reported by Hu [ 90 ] is that the polymer matrix of NC combusts firstly due to the low decomposition temperature (~210 °C); then, the loaded particles of AgIO 3 /CB were initiated to a secondary flame, followed by the formation of AgI nanoparticles, which serve as cloud seeding nuclei. Wang [ 91 ] employed mesoporous SiO 2 particles (~0.9 μm diameter), an inert material with low thermal conductivity, as additives to enhance the reactivity of Al/PVDF films. The added particles not only catalyzed the decomposition of Al/PVDF by releasing more HF but also served as embedded ignition points with more thermal feedback to increase the pressurization rates and burning rates by up to 3 times (5 wt% addition).…”
Section: Energetic Films (2d Ems)mentioning
confidence: 99%
“…A contrasting phenomenon reported by Hu [ 90 ] is that the polymer matrix of NC combusts firstly due to the low decomposition temperature (~210 °C); then, the loaded particles of AgIO 3 /CB were initiated to a secondary flame, followed by the formation of AgI nanoparticles, which serve as cloud seeding nuclei. Wang [ 91 ] employed mesoporous SiO 2 particles (~0.9 μm diameter), an inert material with low thermal conductivity, as additives to enhance the reactivity of Al/PVDF films. The added particles not only catalyzed the decomposition of Al/PVDF by releasing more HF but also served as embedded ignition points with more thermal feedback to increase the pressurization rates and burning rates by up to 3 times (5 wt% addition).…”
Section: Energetic Films (2d Ems)mentioning
confidence: 99%
“…While fluoropolymers have been used as oxidizers in energetic materials, there has been limited research on how the electromechanical properties influence the combustion properties 15–18 . Specifically, tuning the impact sensitivity, burning rate and other combustion properties in fluoropolymer bound energetics by using piezoelectricity and flexoelectricity has yet to be fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…16 While fluoropolymers have been used as oxidizers in energetic materials, there has been limited research on how the electromechanical properties influence the combustion properties. [15][16][17][18] Specifically, tuning the impact sensitivity, burning rate and other combustion properties in fluoropolymer bound energetics by using piezoelectricity and flexoelectricity has yet to be fully studied. Initial research by Row and Groven 15 reported a significant change in the impact sensitivity when a DC voltage was applied to the PVDF/Al and THV/Al reactive systems indicating the electroactive nature.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-supported metal nanoclusters (1–10 nm) have shown potential for applications in electronics, catalysis, energy storage, and sensors. Although many techniques have been developed to decorate metal nanoclusters onto the supporting matrices, achieving a higher surface density while maintaining an ultrasmall size and uniform dispersity is extremely difficult because of the metastable nature and the rapid aggregation of nanoclusters. Simply increasing the nanocluster surface density by adding more nanoclusters onto the host matrix often leads to nanocluster aggregation, uneven dispersion, and further growth of nanoclusters into larger sizes.…”
Section: Introductionmentioning
confidence: 99%